Height information aided 3D real‐time large‐scale underground user positioning. Issue 1 (9th September 2022) - Tang, Chengkai; Zhang, Cunle; Zhang, Lingling; Zhang, Yi; Song, Houbing
Abstract: Due to the cost of inertial navigation and visual navigation equipment and lake of satellite navigation signals, they cannot be used in large‐scale underground mining environment. To solve this problem, this study proposes a large‐scale underground 3D real‐time positioning method with seam height assistance. This method uses the ultra wide band positioning base station as the core and is combined with seam height information to build a factor graph confidence transfer model to realise 3D positioning. The simulation results show that the proposed real‐time method is superior to the existing algorithms in positioning accuracy and can meet the needs of large‐scale underground users.